2017
DOI: 10.1177/1369148117740284
|View full text |Cite
|
Sign up to set email alerts
|

Representation in Wales: An empirical analysis of policy divisions between voters and candidates

Abstract: Politics in Wales is often portrayed as being relatively consensual when compared with the rest of the United Kingdom and enjoying healthy levels of trust between voters and elites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…While it is impossible to validate candidates' self-perceived campaign behaviour, there is evidence to support the reliability of the survey data. It has been shown that the views expressed by successful candidates in the 2016 Welsh Candidate Study are in fact consistent with their subsequent parliamentary activity (Trumm 2018). In addition, the responses to the 2016 Welsh Candidate Study that can be validatede.g., candidacy type, demographics, use of campaign websiteshow no response bias for those respondents whose survey responses can be compared with verified data.…”
Section: Methodsmentioning
confidence: 94%
“…While it is impossible to validate candidates' self-perceived campaign behaviour, there is evidence to support the reliability of the survey data. It has been shown that the views expressed by successful candidates in the 2016 Welsh Candidate Study are in fact consistent with their subsequent parliamentary activity (Trumm 2018). In addition, the responses to the 2016 Welsh Candidate Study that can be validatede.g., candidacy type, demographics, use of campaign websiteshow no response bias for those respondents whose survey responses can be compared with verified data.…”
Section: Methodsmentioning
confidence: 94%